Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".
If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3
y=2x+9 and y=x+6
To solve the following equation by substitution, we need to have the equal sign. This will help us group the knowns and the unknowns.
y= -4x-7 y=3x 3x= -4x-7 3x+4x=7 7x=7 x=1
This is not Calculus.y=7(Already solved)substiute y=7 into y=8xtherefore 7 = 8xtherefore x = 7/8
X = 135 and y = 15 Solved by addition and substitution
-y + y equals 0.
If you mean: 3x-3y = 9 and y-3x = -3 then by adding both equations y = -3 and by substitution x = 0
Y equals 1 and X equals 1
b = y - mx.
y intercept is when x is zero then you solve. slope is rise over run or y -y1 divided by x -x1 you graph by puting the y intersept on the y axis then you take the slope and do the rise then the run
sub x with 0 and solve
For y - 2y - 3y equals 0, y equals 0.
By definition: 4x-10 = 5-x 4x+x = 5+10 5x = 15 x = 3 and y = 2
-3x = 3 + y 3 + y - 5y = -21 -4y = -24 y = 6 x = -3
If you mean: x+7y = 7 and 2x+y = 8 Then by substitution: x = 49/13 and y = 6/13
If: x+y = 8 and 2x-y = 5 Then by adding the equations together: 3x = 13 or x = 13/3 By substitution into the original equations: x = 13/3 and y = 11/3